Magnetic Fields in the Solar Convection Zone - Yuhong Fan (Living Reviews in Solar Physics, 2009)
Active regions on the solar surface are generally thought to originate from a strong toroidal magnetic field generated by a deep seated solar dynamo mechanism operating at the base of the solar convection zone. Thus the magnetic fields need to traverse the entire convection zone before they reach the photosphere to form the observed solar active regions. Understanding this process of active region flux emergence is therefore a crucial component for the study of the solar cycle dynamo. This article reviews studies with regard to the formation and rise of active region scale magnetic flux tubes in the solar convection zone and their emergence into the solar atmosphere as active regions.